Back to baseline in Britain: Adaptation in the BHPS - Andrew E. Clark; Yannis Georgellis (Institute for the Study of Labor (IZA), 2012)
We look for evidence of adaptation in well-being to major life events using eighteen waves of British panel data. Adaptation to marriage, divorce, birth of a child and widowhood appears to be rapid and complete, whereas this is not the case for unemployment. These findings are remarkably similar to those in previous work on German panel data. Equally, the time profiles with life satisfaction as the well-being measure are very close to those using a twelve-item scale of psychological functioning. As such, the phenomenon of adaptation may be a general one, rather than being only found in German data or using single-item well-being measures.
urn:nbn:de:101:1-201207125593
Keywords: I31; J12; J13; J63; J64; 330; life satisfaction; anticipation; adaptation; baseline satisfaction; labour market and life events